The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4041/kjod.2017.47.6.375
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment effects between the modified C-palatal plate and cervical pull headgear for total arch distalization in adults

Abstract: ObjectiveThe purpose of this study was to evaluate the dental and skeletal effects of the modified C-palatal plate (MCPP) for total arch distalization in adult patients with Class II malocclusion and compare the findings with those of cervical pull headgear.MethodsThe study sample consisted of the lateral cephalograms of 44 adult patients with Class II Division 1 malocclusion, including 22 who received treatment with MCPP (age, 24.7 ± 7.7 years) and 22 who received treatment with cervical pull headgear (age, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 25 publications
1
28
1
Order By: Relevance
“…The maxillary incisor in the MCPP group was vertically extruded by 1.03 mm and the mandibular incisor was vertically intruded by 1.11 mm from the HRL, with a net result of 0.64 mm of overbite reduction. This extrusion of the maxillary incisor was consistently described as one of the effects of the MCPP, 20 21 22 and this may suggest that, in challenging deep bite cases, the MCPP should be used with additional bite-opening mechanics, such as intrusion arches or miniscrews, for better vertical control. On the other hand, such movement may serve as an additional advantage when the treatment goal is to increase the amount of overbite or display of maxillary incisors in relation to the upper lip line.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The maxillary incisor in the MCPP group was vertically extruded by 1.03 mm and the mandibular incisor was vertically intruded by 1.11 mm from the HRL, with a net result of 0.64 mm of overbite reduction. This extrusion of the maxillary incisor was consistently described as one of the effects of the MCPP, 20 21 22 and this may suggest that, in challenging deep bite cases, the MCPP should be used with additional bite-opening mechanics, such as intrusion arches or miniscrews, for better vertical control. On the other hand, such movement may serve as an additional advantage when the treatment goal is to increase the amount of overbite or display of maxillary incisors in relation to the upper lip line.…”
Section: Discussionmentioning
confidence: 96%
“…The efficiency of TADs to distalize the whole dentition has been well characterized in the literature. 8 9 10 11 13 15 16 17 18 19 20 21 22 28 29 Reportedly, the amount of maxillary incisor retraction varied from the stationary position to 3.3 mm, mostly falling in the range near 2 to 3 mm. A few studies have even reported mild labial movement of the maxillary incisors after the use of TADs, such as miniscrew-supported skeletal distal jet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many clinical studies 11,25) and biomechanical analyses have investigated posterior movement of the anterior teeth using implant anchorage. Few clinical reports 22,28) and biomechanical analyses 2,3,9,31) regarding en-masse retraction of the entire maxillary or mandibular dentition are available, however. Nonetheless, understanding the biomechanical variables associated with implant anchors in orthodontics is very important, because the height and position of the hooks and implant anchors affect tooth movement.…”
Section: Introductionmentioning
confidence: 99%